AGROTECHNOLOGICAL FEATURES OF GROWING PLANTING MATERIAL LIGUSTRUM VULGARE L. IN THE CONDITIONS OF THE NORTH-EASTERN FOREST-STEPPE OF UKRAINE - Токмань, Владимир (SWorldJournal, 2020)
The necessity of the detailed study of separate elements of the agrotechnics of L. vulgare root planting material cultivation in the conditions of the north-eastern forest-steppe of Ukraine is substantiated. It has been experimentally proved that the abil